2012
DOI: 10.1021/ol2030839
|View full text |Cite
|
Sign up to set email alerts
|

Large-Size Linear and Star-Shaped Dihydropyrazine Fused Pyrazinacenes

Abstract: Linear and star-shaped pyrazinacenes 1a-b and 2 were synthesized via condensation between a new building block 11 and pyrene tetraones or cyclohexaone. Compound 2 represents the largest star-shaped dihydropyrazine fused pyrazinacene reported so far. These largely expanded pyrazinacenes show good solubility and have a strong tendency to aggregate in both solution and thin films, indicating their potential applications for organic electronic devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 42 publications
1
33
0
1
Order By: Relevance
“…For example, Choi, Xiao, Neguyen, and co‐workers employed the 6,7‐dinitroquinoxaline unit as part of synthetic molecular cavitands for supramolecular host‐guest interaction with several substrates from reactions of DCDNQX and resorcinol derivatives. Furthermore, Tong et al . explored reactions of DCDNQX with o‐ diamines and further transformations to synthesize large linear and star‐shaped aza‐acenes with interesting self‐assembly and the potential for application as organic semiconductors.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Choi, Xiao, Neguyen, and co‐workers employed the 6,7‐dinitroquinoxaline unit as part of synthetic molecular cavitands for supramolecular host‐guest interaction with several substrates from reactions of DCDNQX and resorcinol derivatives. Furthermore, Tong et al . explored reactions of DCDNQX with o‐ diamines and further transformations to synthesize large linear and star‐shaped aza‐acenes with interesting self‐assembly and the potential for application as organic semiconductors.…”
Section: Methodsmentioning
confidence: 99%
“…Chan and Chi et al reported a convenient synthesis of large linear and star‐shaped poly(aza)acenes containing fused pyrazine/dihydropyrazine units by the condensation reaction between the new building block, alkylated dihydrotetraazatetracene 1,2‐diamine 162 , and pyrene tetraones ( 163a , b ) or cyclohexaone ( 118 ) (Scheme ) . These azatriphenylene derivatives were reported for the first time as largest star‐shaped dihydropyrazine fused pyrazinacenes.…”
Section: Synthetic Approaches Towards Azatriphenylene Derivatives:mentioning
confidence: 99%
“…Recently, N-heteroacenes, [7][8][9][10] in which sp 2 N atoms have been used to replace CH groups in the backbone of the parent oligoacene systems, [11][12][13][14] have attracted a lot of attention because they are synthetically challenge to make, interesting for theoretical studies, and have potential appli-cations in organic field effect transistors (OFETs), organic light-emitting diodes (OLEDs), organic phototransistors, memory devices, and photovoltaic cells. In our recent research, we have demonstrated that N-heteroacenes can act as anion sensors through anion-p interactions.…”
Section: Introductionmentioning
confidence: 99%